1994
DOI: 10.1182/blood.v84.5.1427.bloodjournal8451427
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, placebo-controlled trial of recombinant human granulocyte colony-stimulating factor administration in newborn infants with presumed sepsis: significant induction of peripheral and bone marrow neutrophilia

Abstract: Host defenses in the human neonate are limited by immaturity in phagocytic immunity. Such limitations seem to predispose infected newborns to neutropenia from an exhaustion of the neutrophil reserve. Among the critical defects thus far identified in neonatal phagocytic immunity is a specific reduction in the capacity of mononuclear cells to express granulocyte colony-stimulating factor (G-CSF) after stimulation. However, the safety, pharmacokinetics, and biological efficacy of administration of recombinant hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 0 publications
2
40
0
1
Order By: Relevance
“…A similar finding was reported in bone marrow transplant patients [33]. In a study of neonatal sepsis, rhG-CSF administration was not associated with pulmonary or other organ toxicity [34]. The recent consensus statement by the American Thoracic Society (ATS) [35] has indicated that hospital-acquired pneumonia (HAP) continues to be the number one cause of death from nosocomial infection.…”
Section: Discussionsupporting
confidence: 69%
“…A similar finding was reported in bone marrow transplant patients [33]. In a study of neonatal sepsis, rhG-CSF administration was not associated with pulmonary or other organ toxicity [34]. The recent consensus statement by the American Thoracic Society (ATS) [35] has indicated that hospital-acquired pneumonia (HAP) continues to be the number one cause of death from nosocomial infection.…”
Section: Discussionsupporting
confidence: 69%
“…90 A leukemoid reaction often is associated with infection, inflammation, malignancy, or use of drugs including glucocorticoids, psychiatric medications, and myeloid growth factors. [91][92][93][94][95][96][97][98][99] Therefore, patient history and findings on physical examination dictate whether further laboratory investigation is necessary to determine the cause of the increased WBC count. Further evaluation, if indicated, starts with a PBS that may show circulating blasts (suggesting acute leukemia), leukoerythroblastic results (suggesting myelofibrosis with myeloid metaplasia or other marrow-infiltrating process), or simply left-shifted neutrophilia.…”
Section: Granulocytosismentioning
confidence: 99%
“…12 Promyelocytes and myelocytes were referred to as the morphologically identifiable neutrophil proliferative pool with proliferative potential, whereas metamyelocytes, bands and segmented neutrophils, a group of matured cells, were referred to as the morphologically identifiable neutrophil storage pool. 13,14…”
Section: Collection Of Peripheral Blood and Bone Marrow And Differenmentioning
confidence: 99%